2023
DOI: 10.3390/jof9040499
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Aspergillus niger Aquaporins Involved in Hydrogen Peroxide Signaling

Abstract: Aspergillus niger is a robust microbial cell factory for organic acid production. However, the regulation of many industrially important pathways is still poorly understood. The regulation of the glucose oxidase (Gox) expression system, involved in the biosynthesis of gluconic acid, has recently been uncovered. The results of that study show hydrogen peroxide, a by-product of the extracellular conversion of glucose to gluconate, has a pivotal role as a signaling molecule in the induction of this system. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In this study, the observed results were not validated by qPCR, as previous experiments by us and other groups have shown the validity of RNA-seq methods for Aspergillus spp. ([ 29 , 36 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ]). In addition, the benchmark study conducted by Evereart et al, 2017 (Sci Rep) [ 82 ] showed a high concordance (~80%) between RNA-seq and qPCR data for various workflows and mapping tools.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the observed results were not validated by qPCR, as previous experiments by us and other groups have shown the validity of RNA-seq methods for Aspergillus spp. ([ 29 , 36 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ]). In addition, the benchmark study conducted by Evereart et al, 2017 (Sci Rep) [ 82 ] showed a high concordance (~80%) between RNA-seq and qPCR data for various workflows and mapping tools.…”
Section: Discussionmentioning
confidence: 99%
“…Aquaglyceroporins, which permeate small uncharged solutes and consequentially do not mediate ion currents, are expressed in the membrane of filamentous fungi [ 35 ]. Recently, seven homologues of the aquaglyceroporins have been identified in Aspergillus [ 36 ], but transport of small solutes has not been measured, except for the channel involvement in the hydrogen peroxide efflux.…”
Section: Discussionmentioning
confidence: 99%